The role of algorithmic thinking development in the learning of elementary school pupils aged 10–13 - Černochová, Miroslava; Selcuk, Hasan; Svoboda, Milan (Epistemological Approaches to Digital Learning in Educational Contexts, 2020)
The chapter presents a case study aimed to identify changes in Czech elementary school pupils’ algorithmic thinking through programming in Scratch. The study was carried out in 2017/18 with 48 pupils in Grade 5 and 6 at an elementary school in Prague with Informatics as a compulsory subject. To identify the impact of Scratch’s activities on pupils’ algorithmic thinking, a set of 16 tasks was proposed for tests A1 and A2. Pupils were tested at the beginning (test A1) and at the end of the case study (test A2). By comparing the results of both, it was possible to discover whether Scratch’s activities had influenced the pupils’ algorithmic thinking. Practically all pupils achieved better results in the A2 test than in A1. The evaluation of the concluding projects using the DrScratch application revealed that the best results were achieved by the pupils with respect to understanding algorithms and in using logical conditions; the worst results related to abstract thinking and parallelism.